2020
DOI: 10.31403/rpgo.v66i2282
|View full text |Cite
|
Sign up to set email alerts
|

Ángulo uterocervical o longitud cervical en la predicción de parto pretérmino inminente en pacientes sintomáticas

Abstract: Objetivo. Comparar el ángulo uterocervical con la longitud cervical en la predicción de parto pretérmino inminente en pacientes sintomáticas. Diseño. Estudio de casoscontroles. Institución. Hospital Central “Dr. Urquinaona”, Maracaibo, Venezuela. Participantes. Pacientes con parto pretérmino en los siguientes 7 días (grupo A) y embarazadas con parto pretérmino más allá de los 7 días (grupo B). Métodos. Al momento del diagnóstico, las pacientes fueron evaluadas utilizando ecografía transvaginal y fueron seguida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 21 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…After excluding duplicates and ineligible studies, 22 studies were included in the qualitative analysis, including 11 prospective cohort studies, 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 7 retrospective cohort studies, 24 , 25 , 26 , 27 , 28 , 29 , 30 and 4 case-control studies. 31 , 32 , 33 , 34 Of note, 1 study was not included in the meta-analysis because of incomplete data. 28
Figure 1 MOOSE flow diagram for new systematic reviews of observational studies Adapted from Stroup.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After excluding duplicates and ineligible studies, 22 studies were included in the qualitative analysis, including 11 prospective cohort studies, 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 7 retrospective cohort studies, 24 , 25 , 26 , 27 , 28 , 29 , 30 and 4 case-control studies. 31 , 32 , 33 , 34 Of note, 1 study was not included in the meta-analysis because of incomplete data. 28
Figure 1 MOOSE flow diagram for new systematic reviews of observational studies Adapted from Stroup.
…”
Section: Resultsmentioning
confidence: 99%
“…All 22 studies included in the qualitative analysis compared UCA in sPTB and term births, with 18 studies showing a statistically significant difference 13 , 15 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 27 , 29 , 30 , 31 , 32 , 33 , 34 and 4 studies showing no difference. 14 , 17 , 26 , 28 Of note, 21 studies were included in the quantitative analysis, as shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The higher sensitivity compared to our results obtained from the measures of our 1st visit can be attributed to the gestational age when the measures were taken being higher than our study (median gestational age was 33 weeks) while the sensitivity was very close when measures were compared with the second visit (72.1% vs 68.1%). Regarding the uterocervical angle, an acute angle reinforces the closure of the endocervical canal, while a more obtuse angle may facilitate the opening of the cervix (23); this could be the reason why Luechathananon et al, obtained a higher cutoff value compared to our study (110.97 ° vs 89.81 ° or 81) (22). In contrast to our study, results obtained by Wagner et al, showed that the uterocervical angle is not a useful measure for the prediction of preterm birth, the included patients in this study accounted for that difference as they included patients with regular uterine contractions and cervical length less than 25mm which indicated a very high risk for preterm delivery; an obtuse uterocervical angle was predominant in the three study groups that were delivery within 2 days, 3-7 days and after 7 days with corresponding median UCA angle of 108.5, 108°, and 107.3° (24).…”
Section: Discussionmentioning
confidence: 99%